Brain Gymnastics Video Media to Increase Learning Concentration for Third Grade Students - Putu Juwita Cahyanti; Kadek Suranata; Kadek Yudiana (Thinking Skills and Creativity Journal, 2024)
This study was motivated by the low level of learning concentration among third-grade elementary students, as identified through the initial results of the Grid Concentration Test, which showed that most students were categorized as "Low" to "Very Low." The purpose of this study was to develop a brain gymnastic video as a medium to enhance students’ learning concentration. The research involved 39 third-grade students and employed a development research method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The development process included expert validation from subject matter experts, instructional design experts, and media experts, as well as individual and small group trials. Validation results indicated that the brain gym video met a very high standard of quality, with scores of 98.33% from both the subject matter and design experts, and 97.5% from the media expert. The effectiveness test, using a paired sample t-test, showed a statistically significant improvement in concentration (t-calculated = 28.303 > t-table = 2.026). These findings indicate that the brain gym video is effective in improving students' learning concentration. The implication of this study is that brain gym videos can serve as an innovative learning medium that effectively enhances students’ focus and attention in primary education settings.